Exercices de déprise - Marianne Massin (Methodos, 2021)
While repetitive exercise is most often seen as a method to insure and reinforce mastery, this article proposes, on the contrary, to underline the necessary qualities of “detachment” as it applies in, by and for the notion of artistic exercise. It is only by examining exercise from the vantage point of these three prepositions that the phenomenon can be understood in its fullest aspect. Through the analysis of works of art as well as literary practices, this proposed oxymoron will be developed using the double meaning of the verb “to detach” (déprendre) – its transitive meaning, to isolate something, and its intransitive and pronominal meaning, to detach oneself from. Thus understood, the exercise in art could be compared to a "spiritual exercise". Ultimately, this comparison invites a nuanced examination, which we will undertake using the texts of P. Hadot, V. Chklovski, and C. Ginzburg.